Rooms versus F&B: How changes in operations contribute to hotel productivity - Yoo Ri Kim; Shih-Chuan Lin (Annals of Tourism Research Empirical Insights)
This study investigates how different operational responses impact hotel productivity change, specifically investigating the importance of F&B operations in comparison to room operations and applying the case of the Taiwanese hotel industry, conducting 93 international tourist hotels from April 2012 to March 2021. Using regression discontinuity design analysis, first, the study finds a significant causal impact of COVID-19 travel restrictions on hotel operations. Second, using the control function methods, findings show that F&B operation is a more efficient strategy compared to rooms to recover hotel productivity from crises. This research provides insights into how hotels can reallocate their operational resources in response to crises and offers an alternative measure of productivity for the hotel industry.